Meningkatkan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Melalui Kegiatan Gerak Dan Lagu Di PAUD Nurul Ilmi BSI Desa Cibinong Kecamatan Gunungsindur-Bogor - Siti siti Maemunah (UNIVERSITAS PGRI MADIUN, 2022)
This study aims to improve gross motor skills of early childhood through movement and song activities. This research uses classroom action research (CAR) using the Kemmis MC Taggart model which consists of planning, implementing, observing, and reflecting. The object of this research in PAUD Nurul Ilmi BSI uses Limited Face-to-face Learning (PTM). With the subject of children aged 5-6 years as many as 12 children. Based on the results obtained before the pre-cycle, the average gross motor skills of children were only 35.7%. This is still quite low. Then after conducting classroom action research in the first cycle, it showed an increase in children's gross motor skills to 47.7%. And in the second cycle there was a significant increase in children's gross motor skills to 80%. From the movement and song learning activities during the Covid-19 pandemic, it was stated that they were able to improve the gross motor skills of early childhood.Keywords: Gross Motor, Motion and Song